2010
DOI: 10.3399/bjgp10x515070
|View full text |Cite
|
Sign up to set email alerts
|

Low exercise among children with asthma: a culture of over protection? A qualitative study of experiences and beliefs

Abstract: Background: Research shows that children are insufficiently active in most affluent societies. Although children with asthma may particularly benefit from physical activity, they are less active than their peers. Aim: To explore the reasons for low physical activity levels among children with asthma and to identify strategies to improve activity. Design of study: A qualitative study using in-depth interviews and focus groups. Setting: Six GP practices, a Paediatric Respiratory Unit, and four schools in Tayside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 30 publications
4
35
0
4
Order By: Relevance
“…The same study also reported that 37% of mothers reported that exercise was dangerous for children with asthma, but there was no evidence of an association between the severity of the child's asthma and his or her physical activity. Qualitative data from Scotland have shown that many parents and school staff were very anxious about children with asthma being physically active, and that physical activity was perceived as a threat to asthma control 24. Thus, there is a clear need to communicate to parents and school staff that physical activity is possible for children with asthma and the challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same study also reported that 37% of mothers reported that exercise was dangerous for children with asthma, but there was no evidence of an association between the severity of the child's asthma and his or her physical activity. Qualitative data from Scotland have shown that many parents and school staff were very anxious about children with asthma being physically active, and that physical activity was perceived as a threat to asthma control 24. Thus, there is a clear need to communicate to parents and school staff that physical activity is possible for children with asthma and the challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative data from Scotland have shown that many parents and school staff were very anxious about children with asthma being physically active, and that physical activity was perceived as a threat to asthma control. 24 Thus, there is a clear need to communicate to parents and school staff that physical activity is possible for children with asthma and the challenge. The challenge is to build on current efforts to find more effective, easier to implement and sustain ways of helping this group to be more active more often.…”
Section: Discussionmentioning
confidence: 99%
“…Older subjects seems less sensible of parental support (19). Concerning parental restrictions to PA by fear of breathlessness in children and adolescents with asthma (15,16), one may also expect the association to be negative. Lack of negative significant association of parental support may thereby be interpreted as satisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, van Gent et al (10) did not found lower level of VPA based on both self-reports and objective recordings, and neither did Nystad (11) at any level of exercise frequency or exercise hours a week in asthma based on self-reports. Even though asthma control and severity are associated with level of PA (1,6,7), and that increased intensity and exercise load is associated with bronchoconstriction (12), there is also evidence that psychosocial and socio-demographical factors and knowledge/competence are important for level of physical activity in children and adolescents with asthma (1,(13)(14)(15)(16)(17)(18). Parents observing shortness of breath in their child may lead them to restrain their children from exertion (14), with subsequent increasing fear of breathlessness followed by personal or parental restrictions (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The first is about asthmatic school children in Dundee, and their own, their parents', and their teachers' perceptions of their ability to take part in physical activity. 3 From this paper it is clear that there are many false limiting beliefs among these children about their asthma, some of which arise from what we as doctors have told them. Is this another example of a way in which doctors can create iatrogenic harm?…”
Section: The Exercise Prescriptionmentioning
confidence: 99%